Constitutive androstane receptor induced-hepatomegaly and liver regeneration is partially via yes-associated protein activation - Yue Gao; Shicheng Fan; Hua Li; Yiming Jiang; Xinpeng Yao; Shuguang Zhu; Xiao Yang; Ruimin Wang; Jianing Tian; Frank J. Gonzalez; Min Huang; Huichang Bi (Elsevier, 2021)
The constitutive androstane receptor (CAR, NR3I1) belongs to nuclear receptor superfamily. It was reported that CAR agonist TCPOBOP induces hepatomegaly but the underlying mechanism remains largely unknown. Yes-associated protein (YAP) is a potent regulator of organ size. The aim of this study is to explore the role of YAP in CAR activation-induced hepatomegaly and liver regeneration. TCPOBOP-induced CAR activation on hepatomegaly and liver regeneration was evaluated in wild-type (WT) mice, liver-specific YAP-deficient mice, and partial hepatectomy (PHx) mice. The results demonstrate that TCPOBOP can increase the liver-to-body weight ratio in wild-type mice and PHx mice. Hepatocytes enlargement around central vein (CV) area was observed, meanwhile hepatocytes proliferation was promoted as evidenced by the increased number of KI67+ cells around portal vein (PV) area. The protein levels of YAP and its downstream targets were upregulated in TCPOBOP-treated mice and YAP translocation can be induced by CAR activation. Co-immunoprecipitation results suggested a potential protein-protein interaction of CAR and YAP. However, CAR activation-induced hepatomegaly can still be observed in liver-specific YAP-deficient (Yap-/-) mice. In summary, CAR activation promotes hepatomegaly and liver regeneration partially by inducing YAP translocation and interaction with YAP signaling pathway, which provides new insights to further understand the physiological functions of CAR.